Detecting Differential Items Functioning of a Criterion-Referenced Test for a Calculus Course (1) According to the modern theory; for students at Sana’a University according to the variables (gender, system, college) - Abo Hadi, Sawsan Hasan; A’alem, Tawfiq Ali (Journal of Educational and Psychological Sciences, 2023)
This study aimed to Detecting differential items functioning of a Criterion- Referenced Test for a Calculus Course (1) according to the variable (gender, system and college). The test is constructed according to the modern theory. To achieve this goal designed a test constitutes of (40) multiple-choice items. The test applied at the academic year 2020-2021, on a sample of (240) Sana'a University students were randomly chosen. The results of the statistical program (Bilog-MG3) verified that 35 test items fit the one parameters model. Findings indicated that: (4) items showed differential functioning according to the gender variable related to male students. (6) items showed differential functioning according to the system variable distributed equally. (6), (3) items showed differential functioning according to the college variable (Education, Engineering), (Computer, Engineering) respectively distributed in different numbers for college of Education and Computer. The study recommendation indicates to the importance of checking items differential functioning especially when comparison between groups that have different properties.
Keywords: Differential Item Functioning; Criterion Referenced Test; Calculus Course (1); Modern Theory; One Parameters Model